United States of America. Significant achievements 2010-2017 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The main activities carried out by the Institute in the United States are identified, during the period from 2010 to 2017, with respect to the needs and interests of the country, strengthening issues such as agricultural trade, biotechnology, public policies, water management, natural resource management, fruit loss management, risk management, organic agriculture, innovation, sustainability, research, germplasm, health and food safety, through the Codex Alimentarius, resilience against climate change and pest control, such as rust of coffee and insects, through biological methods. Likewise, work was done on reducing poverty, financial assistance, insurance and improving the production chains of mangoes and avocados. Finally, support was given to the control of noncommunicable diseases and communicable diseases, such as tuberculosis, flu, and the H1N1 virus.